Coping with Change: International Differences in the Returns to Skills - Eric A. Hanushek; Guido Schwerdt; Simon Wiederhold; Ludger Woessmann (Institute for the Study of Labor (IZA), 2016)
Expanded international data from the PIAAC survey of adult skills allow us to analyze potential sources of the cross-country variation of comparably estimated labor-market returns to skills in a more diverse set of 32 countries. Returns to skills are systematically larger in countries that have grown faster in the recent past, consistent with models where skills are particularly important for adaptation to dynamic economic change.
Keywords: J31; I20; O15; 330; economic growth; returns to education; cognitive skills; international comparisons